Time Domain and Spatially Resolved NMR: Advanced Applications to Porous Media of Interest to Environmental Sustainability and Human Healthcare - Brizi, Leonardo <1986> (Alma Mater Studiorum - Università di Bologna, 2016)
Time-domain and spatially resolved NMR techniques developed in the field of Magnetic Resonance for fluids in Porous Media have been successfully applied to study various porous systems of different nature and origin, containing hydrogenous fluids. The unifying principle of this work is showing how the NMR analyses performed with these techniques can be extended to a multiplicity of porous material and how these methods are able to investigate the structure of the pore space and other features in a non-destructive manner, on the intact sample, from the macroscopic scale to the nanometric one. In particular, NMR relaxometry has been applied to the study of coral skeleton modifications due to Ocean Acidification. Skeletal porosity over length scales spanning from tens of nanometers to tens of micrometers was evaluated, giving precious information about the capability of coral to acclimate under adverse conditions. Another application of relaxometry was about the study of water compartmentalization for monitoring viability and water compartmentalization of cell populations kept under stress conditions. Parallel experiments performed by MRI and NMR single-sided techniques were executed in order to test the efficiency of protectives and consolidants applied for preserving and restore carbonate building materials of interest to Cultural Heritage. The study confirmed that quantitative MRI and NMR profiles are excellent tools for evaluating the performance of protective compounds. On the same samples the 2D NMR techniques were settled and implemented, showing the great potentiality in order to detect the pore space structure and in particular the surface-to-volume ratio, the tortuosity and the connectivity of the medium. The results of this thesis demonstrate that the same experimental NMR procedures can be successfully applied to perform researches in important topics that deal with the Sustainability of Environment and Human Healthcare.